O atendimento educacional especializado (AEE) da Escola estadual Girassol de tempo integral Combinado, Município de Combinado - (TO) - Alves, Valéria Sousa (Universidade Federal do Tocantins, 2023)
The present work entitled Specialized Educational Service (AEE): from the Girassol State School of Integral Time Combined, located in the municipality of Combinado (TO), aims to analyze the methods and characteristics of Specialized Educational Service (AEE) in this unit teaching, as a space for the construction of school inclusion. Therefore, a historical overview of Special Education in Brazil and reflections on the inclusion process were carried out. The AEE is guaranteed by law at all levels of education in basic education and aims to offer referrals to students with disabilities, developmental disorders and high giftedness skills in a Multifunctional Resource Room (SRM). The research was based on a qualitativos approaches research, with the use of instruments: observariam of the virtual context of the Specialized Educational Service (AEE) room and through the application of a questionnaire to the AEE room teacher and the mother of a student frequent in the resource room. The work provided information about the teaching-learning process and the inclusion of AEE students in that school, showing the importance of inclusion in the students' teaching and learning process. Note that the inclusion of students in regular schools in the public education system should be seen as a new paradigm. Do not let the Laws remain only on paper, but put them into practice from the perspective of an inclusive, egalitarian education, in defense of all students to be together, learning and participating, without any type of discrimination.